A new nutraceutical (Livogen Plus®) improves liver steatosis in adults with non-alcoholic fatty liver disease - Yvelise Ferro; Roberta Pujia; Elisa Mazza; Lidia Lascala; Oscar Lodari; Samantha Maurotti; Arturo Pujia; Tiziana Montalcini (Journal of Translational Medicine, 2022)
Abstract Background Currently, there is no approved medication for non-alcoholic fatty liver disease management. Pre-clinical and clinical studies showed that several bioactive molecules in plants or foods (i.e., curcumin complex, bergamot polyphenol fraction, artichoke leaf extract, black seed oil, concentrate fish oil, picroliv root, glutathione, S-adenosyl-l-methionine and other natural ingredients) have been associated with improved fatty liver disease. Starting from these evidences, our purpose was to evaluate the effects of a novel combination of abovementioned nutraceuticals as a treatment for adults with fatty liver disease. Methods A total of 140 participants with liver steatosis were enrolled in a randomized, double-blind, placebo controlled clinical trial. The intervention group received six softgel capsules daily of a nutraceutical (namely Livogen Plus®) containing a combination of natural bioactive components for 12 weeks. The control group received six softgel capsules daily of a placebo containing maltodextrin for 12 weeks. The primary outcome measure was the change in liver fat content (CAP score). CAP score, by transient elastography, serum glucose, lipids, transaminases, and cytokines were measured at baseline and after intervention. Results After adjustment for confounding variables (i.e., CAP score and triglyceride at baseline, and changes of serum γGT, and vegetable and animal proteins, cholesterol intake at the follow-up), we found a greater CAP score reduction in the nutraceutical group rather than placebo (− 34 ± 5 dB/m vs. − 20 ± 5 dB/m, respectively; p = 0.045). The CAP score reduction (%) was even greater in those with aged 60 or less, low baseline HDL-C, AST reduction as well as in men. Conclusion Our results showed that a new combination of bioactive molecules as nutraceutical was safe and effective in reducing liver fat content over 12 weeks in individuals with hepatic steatosis. Trial registration ISRCTN, ISRCTN70887063. Registered 03 August 2021—retrospectively registered, https://doi.org/10.1186/ISRCTN70887063